Central bank independence, accountability, and transparency : a global perspective - Laurens, Bernard; Arnone, Marco; Segalotto, Jean-François. (Houndmills, Basingstoke ; New York , NY : Palgrave Macmillan, 2009)
In the context of the current global financial crisis, where central banks have taken a key role in preserving systemic stability, this book brings together the three pillars of central bank governance and provides a joint analysis of central bank independence, accountability and transparency. It offers a comprehensive review of the literature, and proposes new indices and calculates new measures of the three pillars of central bank governance, which are afterwards applied to global central banks. This volume argues that, while it may not always be desirable for the central bank to supervise financial institutions, there is a strong case for all central banks not to overlook financial stability issues. This book offers data sets on these topics, and discusses the evolving role of central banks.--Publisher's description.
Includes bibliographical references (p. 256-263) and index.
rua 28/11/13
Loans
Keywords: Banks and banking-Central.; Central bank independence; Accountability; Transparency